2008
DOI: 10.1211/ijpp.16.3.0008
|View full text |Cite
|
Sign up to set email alerts
|

A study of unprevented dispensing incidents in Welsh NHS hospitals

Abstract: Objective To monitor unprevented dispensing incidents in NHS hospitals by identifying incident types, drugs involved and factors that may have contributed to the occurrence of incidents. Setting All 20 Welsh NHS hospitals (15 district general; 2 teaching; 2 psychiatric and 1 other specialist hospital). Method Unprevented dispensing incidents that occurred between January 2003 and December 2004 were reported and analysed using a validated method. Incident rate was calculated for those hospitals that provided bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(79 citation statements)
references
References 26 publications
(39 reference statements)
2
77
0
Order By: Relevance
“…[1] However, the UK NPSA patient safety taxonomy for unprevented and prevented patient safety incidents was only adopted by four of the reviewed UK papers undertaken after 2004. [44,47,48,72] The World Health Organization is currently developing global patient safety taxonomy. [77,78] Therefore, it is anticipated that the World Health Organization taxonomy will facilitate consistent data collection, sharing of patient safety information and the development of global solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] However, the UK NPSA patient safety taxonomy for unprevented and prevented patient safety incidents was only adopted by four of the reviewed UK papers undertaken after 2004. [44,47,48,72] The World Health Organization is currently developing global patient safety taxonomy. [77,78] Therefore, it is anticipated that the World Health Organization taxonomy will facilitate consistent data collection, sharing of patient safety information and the development of global solutions.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[33][34][35]43,46,72] Five papers investigated the impact of automation on the types of dispensing errors. [42,[44][45][46][47] Three papers analysed prevented dispensing incidents [42,45,46] and two papers examined unprevented dispensing incidents. [44,47] Adedoye [45] reported that the most common prevented dispensing incidents associated with an automated dispensing system were labelling errors (76%, n = 81) and drug/content errors (18%, n = 20).…”
Section: Incidence In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the identified studies, the majority were published in either the USA (n = 15) [43][44][45][46][47][54][55][56]58,59,61,[64][65][66]70], or the UK (n = 14) [37,41,42,[48][49][50]52,53,60,68,69,[71][72][73]. Two studies were conducted in Canada [38][39][40], two in Australia [62,63] and two in Europe [57,67].…”
Section: Country Of Publicationmentioning
confidence: 99%
“…Dispensing errors are sub-divided into unprevented and prevented dispensing incidents. Unprevented dispensing incidents (errors) are "dispensing errors detected and reported after medication has left the pharmacy, which may or may not lead to patient harm 1,2 ". Prevented dispensing incidents (near-misses) are "dispensing errors detected during dispensing before the medication has left the pharmacy [1][2][3] ".…”
Section: Introductionmentioning
confidence: 99%